Connect and Celebrate the Great Mother Online: The Ritual Creativity of Contemporary Pagans in Portugal and the United Kingdom during the COVID-19 Restrictions - Martins, Joana (Nova religio, 2023)
Rituals are creative embodied and emotional practices and are central in the lived spiritual and religious experience of contemporary Pagans, strengthening their community ties. In March 2020, with the outbreak of COVID-19 and the consequent restrictions raised by the Portuguese and British governments, isolation and the impossibility of onsite ritualization led to alternative forms of engagement and relationality within the community. Contemporary Pagans used online and digital tools and developed several strategies to care for and offer emotional and spiritual support during these challenging times. This article, based on online fieldwork among Portuguese and British contemporary Pagans during 2020, argues that Pagans embraced online forms of ritualization as an answer to the uncertainty of the period, feeling connected with each other even without the embodied, sensorial, and nature-based experience of onsite ritualization. It examines the challenges that these forms of engagement raise to the academic study of Contemporary Paganism.